Mayotte seismic crisis: building knowledge in near real-time by combining land and ocean-bottom seismometers, first results. Issue 2 (24th September 2021) - Saurel, Jean-Marie; Jacques, Eric; Aiken, Chastity; Lemoine, Anne; Retailleau, Lise; Lavayssière, Aude; Foix, Océane; Dofal, Anthony; Laurent, Angèle; Mercury, Nicolas; Crawford, Wayne; Lemarchand, Arnaud; et al.
SUMMARY: The brutal onset of seismicity offshore Mayotte island North of the Mozambique Channel, Indian Ocean, that occurred in May 2018 caught the population, authorities and scientific community off guard. Around 20 potentially felt earthquakes were recorded in the first 5 d, up to magnitude M w 5.9. The scientific community had little pre-existing knowledge of the seismic activity in the region due to poor seismic network coverage. During 2018 and 2019, the MAYOBS/REVOSIMA seismology group was progressively built between four French research institutions to improve instrumentation and data sets to monitor what we know now as an on-going exceptional submarine basaltic eruption. After the addition of 3 medium-band stations on Mayotte island and 1 on Grande Glorieuse island in early 2019, the data recovered from the Ocean Bottom Seismometers were regularly processed by the group to improve the location of the earthquakes detected daily by the land network. We first built a new local 1-D velocity model and established specific data processing procedures. The local 1.66 low VP / VS ratio we estimated is compatible with a volcanic island context. We manually picked about 125 000 P and S phases on land and sea bottom stations to locate more than 5000 events between February 2019 and May 2020. The earthquakes outline two separate seismic clusters offshore that we named Proximal and Distal. The Proximal cluster, located 10 km offshore Mayotte eastern coastlines, is 20–50 km deep and has a cylindrical shape. The Distal cluster start 5 km to the east of the Proximal cluster and extends below Mayotte's new volcanic edifice, from 50 to 25 km depth. The two clusters appear seismically separated, however our data set is insufficient to firmly demonstrate this.